Implementation Of The West Java Provincial Government's Sister Province Cooperation Policy With Shizuoka Prefecture, Japan - Fajar Aprillianto Rustandi; Dadang Suwanda; Dyah Poespita Ernawati (Sean Institute, 2024)
The West Java Provincial Government is carrying out sister province cooperation with Shizuoka Prefecture, Japan, in which there is a work plan in the field of employment to improve human resources and increase labor absorption. The aim of this research is to describe the implementation of the West Java Provincial Government's sister province cooperation policy with Shizuoka Prefecture, Japan. This research uses a qualitative method with a descriptive approach. The results of the research show that interests are influenced by the interests of both parties, there are benefits that 35 people are already actively working in Shizuoka Japan, the training participants can speak Japanese fluently and write hiragana letters quite well, decision making is correct by obtaining approval from the Government and DPRD, the program implementer has been listed in the work plan document but at the technical level it is not written in the form of a Working Team Decree, the proposal for implementing cooperation has not gone through a process formulated by the Regional Cooperation Coordination Team, the work mechanism is still hierarchical, compliance and response from implementers is quite good . Inhibiting factors are differences in language, work culture and bureaucracy, the Covid-19 pandemic, limited budget and human resources. Supporting factors include trust and good relations between both parties, as well as work motivation. Efforts are made to provide foreign language translation services and the use of information and communication technology.